Myocarditis Elicits Dendritic Cell and Monocyte Infiltration in the Heart and Self-Antigen Presentation by Conventional Type 2 Dendritic Cells - Van der Borght, Katrien; Scott, Charlotte L.; Martens, Liesbet; Sichien, Dorine; Van Isterdael, Gert; Nindl, Veronika; Saeys, Yvan; Boon, Louis; Ludewig, Burkhard; Gillebert, Thierry C.; Lambrecht, Bart N. (Frontiers in Immunology, 2018)
Autoimmune myocarditis often leads to dilated cardiomyopathy. Although T cell reactivity to cardiac self-antigen is common in the disease, it is unknown which antigen presenting cell (APC) triggers autoimmunity. Experimental autoimmune myocarditis (EAM) was induced by immunizing mice with α-myosin loaded bone marrow APCs cultured in GM-CSF. APCs found in such cultures include conventional type 2 CD11b+ cDCs (GM-cDC2s) and monocyte-derived cells (GM-MCs). However, only α-myosin loaded GM-cDC2s could induce EAM. We also studied antigen presenting capacity of endogenous type 1 CD24+ cDCs (cDC1s), cDC2s and MCs for α-myosin-specific TCR-transgenic TCR-M CD4+ T cells. After EAM induction, all cardiac APCs significantly increased and cDCs migrated to the heart-draining mediastinal lymph node. Primarily cDC2s presented α-myosin to TCR-M cells and induced Th1/Th17 differentiation. Loss of IRF4 in Irf4fl/fl.Cd11cCre mice reduced MHCII expression on GM-cDC2s in vitro and cDC2 migration in vivo. However, partly defective cDC2 functions in Irf4fl/fl.Cd11cCre mice did not suppress EAM. MCs were the largest APC subset in the inflamed heart and produced pro-inflammatory cytokines. Targeting APC populations could be exploited in the design of new therapies for cardiac autoimmunity.